Pengaruh Media Promosi Internet dan Personal Selling terhadap Keputusan Pembelian Produk Skin Care SR Olshop di Kota Makassar - Samsinar; Salamun Pasda; Muhammad Hasan; M. Ihsan Said Ahmad; Muhammad Dinar (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
This study examines how the influence of internet promotion media and personal selling on the purchasing decisions of SR Olshop skin care products in Makassar City. This research is categorized as a qualitative descriptive study with a population of 49 people who are consumers of SR Olshop skin care products in Makassar City, especially in the Antang area, Kec. Manggala. The data was collected by means of observation, questionnaires and documentation. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the promotional media variable had a positive and significant effect on the purchasing decision of SR Olshop skin care products in Makassar City, while the personal selling variable had a negative and insignificant effect on the purchase of SR Olshop skin care products in Makassar City.